Chlorine Identification in Rice Samples through a Method Validation Approach using Cyclic Voltammetry with Platinum Electrodes - Thorikul Huda; Riyanto Riyanto; Rini Rahayu (Universitas Tadulako, 2022)
Determination of chlorine in rice samples with a method validation approach using cyclic voltammetry based on platinum electrodes has been conducted. This study aimed to determine whether the cyclic voltammetry method with platinum electrodes is acceptable and can be recommended for routine chlorine testing in the laboratory. The basis of the analysis is the reduction reaction of hypochlorite ions to chloride ions. The initial step taken by optimizing the electrolyte with the optimal electrolyte for testing is a pH 7 phosphate buffer solution. Method validation parameters consist of determining linearity, detection limit, quantitation limit, repeatability, recovery, and measurement uncertainty. The range of standard solutions used for testing was from 10 mg/L to 150 mg/L and analyzed at a rate of 0.1 V/s. Linearity is determined based on the calculation of the coefficient of determination (R2) of 0.998, while the limits for detection and quantization are 7.49 mg/L and 24.96 mg/L, respectively. Repeatability is determined by calculating the relative standard deviation with a result of 1.77% while for recovery it is obtained at 88.19%. The result of the chlorine content test for rice samples was 0.011% with a measurement uncertainty value of 0.0011%. The major contributor to uncertainty came from the concentration of the calibration curve plot of 87.91%.